Two Decades of Dust Evolution in SN 2005af through JWST, Spitzer, and Chemical Modeling - Martínez, Laureano (2025)
The evolution of dust in core-collapse supernovae (SNe), in general, is poorly constrained owing to a lack of infrared observations a few years after explosion. Most theories of dust formation in SNe heavily rely only on SN 1987A. In the last two years, the James Webb Space Telescope (JWST) has enabled us to probe the dust evolution in decades-old SNe, such as SN 2004et, SN 2005ip, and SN 1980K. In this paper, we present two decades of dust evolution in SN 2005af, combining early-time infrared observations with the Spitzer Space Telescope and recent detections by the JWST. We have used a chemical kinetic model of dust synthesis in SN ejecta to develop a template of dust evolution in SN 2005af. Moreover, using this approach, for the first time, we have separately quantified the dust formed in the pre-explosion wind that survived after the explosion and the dust formed in the metal-rich SN ejecta post-explosion. We report that in SN 2005af, predominantly carbon-rich dust formed in the ejecta, with a total mass of at least 0.02M⊙. In the circumstellar medium, the surviving oxygen-rich dust amounts to about (3–6) × 10−3M⊙, yielding a total dust mass of at least 0.025 M⊙.